Cloud Security Based on PaaS Model - Kumar, Saroj; Kumar, Santosh (International Journal of Computer Sciences and Engineering, 2019)
Paas provide consumers easier way to produce and deploy software and cloud infrastructure [4], thus Paas doubtless occurs the best impact over any other aspect of cloud computing because it brings custom software development to the cloud. National Institute of Standards and Technology describes Paas as: “The capability provided to the consumer to deploy onto the cloud infrastructure consumer-created or acquired applications created using programming languages and tools supported by the provider.”[2]. Thus Paas security which is based on framework, environment, interface and different elements with connected data security. In this paper a secure model is proposed with is based on tokenization and masking technique with key management system. This paper conjointly fulfils the SPI service delivery model and FISMA ACT for PAAS security problems in any cloud service.